Are headache patients who initiate their referral to a neurologist satisfied with the consultation? A population study of 927 patients--the North Norway Headache Study (NNHS) - Bekkelund, Svein Ivar; Salvesen, Rolf (Family Practice, 2001)
Background. Headache is a common problem in primary care. Although most patients are treated by GPs, many are referred to specialist consultation. Knowledge of how the referrals can be improved is therefore an important issue. Objectives. The aim of this study was to determine the relationship between self-initiating referral to a neurologist and the patient's satisfaction with the specialist consultation. Methods. All patients who had been examined by a neurologist for headache within a 2-year period from three neurological centres in North Norway completed a questionnaire. Results. A total of 1052 patients from a population of 1403 headache patients (75%) returned the questionnaire while 927 patients answered questions about initiating the referral to the specialist. Two hundred and twenty patients (24%) initiated the referral to the neurologist themselves; 52% of those who self-initiated the referral were dissatisfied with the specialist consultation compared with 42% of those referred by the doctor, P = 0.002. Chronic headache, tension-type headache (TTH) and daily use of analgesic drugs were associated with dissatisfaction. Conclusions. Patients with headache who initiated the referral to a neurologist themselves were less satisfied with the specialist consultation. Selecting referrals containing proper medical information may improve satisfaction in severe headache patients treated in a neurological practice.